2016
DOI: 10.1186/s13661-016-0587-6
|View full text |Cite
|
Sign up to set email alerts
|

On a parabolic equation related to the p-Laplacian

Abstract: Consider a parabolic equation related to the p-Laplacian. If the diffusion coefficient of the equation is degenerate on the boundary, no matter we can define the trace of the solution on the boundary or not, by choosing a suitable test function, the stability of the solutions always can be established without a boundary condition. MSC: 35K55; 46E35; 35R35

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Here, , Ω is a bounded domain in with appropriately smooth boundary, and at least there is a such that . Zhan [2] had shown that the stability of the solutions to the equation is true, where is distance function, is a constant. The result of [2] is in complete antithesis to that of [1].…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, , Ω is a bounded domain in with appropriately smooth boundary, and at least there is a such that . Zhan [2] had shown that the stability of the solutions to the equation is true, where is distance function, is a constant. The result of [2] is in complete antithesis to that of [1].…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…Zhan [2] had shown that the stability of the solutions to the equation is true, where is distance function, is a constant. The result of [2] is in complete antithesis to that of [1]. So, when the well-posedness of the solutions is considered, the degeneracy of the diffusion coefficient plays an important role.…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…and shown that condition (8) may act as the role as the boundary value condition (3) and ensure the well-posedness of the solutions [12][13][14][15]. Coming back to (1).…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, we prove the stability of the unique weak solution to the Dirichlet problem (2) in the sense that the solutions are controlled by the initial value completely, cf. [1][2][3]. The motivation of this paper contains several aspects.…”
Section: Introductionmentioning
confidence: 99%